pB264, a small, mobilizable, temperature sensitive plasmid from Rhodococcus - Currie Devin H (BMC Microbiology, 2004)
Abstract Background Gram-positive bacteria of the genus Rhodococcus have shown an extraordinary capacity for metabolizing recalcitrant organic compounds. One hindrance to the full exploitation of Rhodococcus is the dearth of genetic tools available for strain manipulation. To address this issue, we sought to develop a plasmid-based system for genetic manipulation of a variety of Rhodococcus strains. Results We isolated and sequenced pB264, a 4,970 bp cryptic plasmid from Rhodococcus sp. B264-1 with features of a theta-type replication mechanism. pB264 was nearly identical to pKA22, a previously sequenced but uncharacterized cryptic plasmid. Derivatives of pB264 replicate in a diverse range of Rhodococcus species, showing that this plasmid does not bear the same host range restrictions that have been exhibited by other theta replicating plasmids. Replication or maintenance of pB264 is inhibited at 37°C, making pB264 useful as a suicide vector for genetic manipulation of Rhodococcus. A series of deletions revealed that ca. 1.3 kb from pB264 was sufficient to support replication and stable inheritance of the plasmid. This region includes two open reading frames that encode functions (RepAB) that can support replication of pB264 derivatives in trans. Rhodococcus sp. B264-1 will mobilize pB264 into other Rhodococcus species via conjugation, making it possible to genetically modify bacterial strains that are otherwise difficult to transform. The cis-acting element (oriT) required for conjugal transfer of pB264 resides within a ca. 0.7 kb region that is distinct from the regions responsible for replication. Conclusion Shuttle vectors derived from pB264 will be useful for genetic studies and strain improvement in Rhodococcus, and will also be useful for studying the processes of theta replication and conjugal transfer among actinomycetes.